2015
DOI: 10.1007/s00425-015-2400-7
|View full text |Cite
|
Sign up to set email alerts
|

Salt intolerance in Arabidopsis: shoot and root sodium toxicity, and inhibition by sodium-plus-potassium overaccumulation

Abstract: Arabidopsis plants in NaCl suffering half growth inhibition do not suffer osmotic stress and seldom shoot Na (+) toxicity; overaccumulation of Na (+) plus K (+) might trigger the inhibition. It is widely assumed that salinity inhibits plant growth by osmotic stress and shoot Na(+) toxicity. This study aims to examine the growth inhibition of Arabidopsis thaliana by NaCl concentrations that allow the completion of the life cycle. Unaffected Col-0 wild-type plants were used to define nontoxic Na(+) contents; Na(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 84 publications
2
40
0
Order By: Relevance
“…Although shoot Na + exclusion is widely acclaimed to be one of the most important salt tolerance mechanisms, both root and shoot Na + accumulation have been shown to affect plant growth under salt stress (Álvarez-Aragón et al, 2016). This study also revealed that under salt stress in Arabidopsis, not only Na + accumulation is the cause for growth impairment, but also K + accumulation.…”
Section: Regulation Of Toxic Na+ Accumulation In the Leaf Bladementioning
confidence: 99%
“…Although shoot Na + exclusion is widely acclaimed to be one of the most important salt tolerance mechanisms, both root and shoot Na + accumulation have been shown to affect plant growth under salt stress (Álvarez-Aragón et al, 2016). This study also revealed that under salt stress in Arabidopsis, not only Na + accumulation is the cause for growth impairment, but also K + accumulation.…”
Section: Regulation Of Toxic Na+ Accumulation In the Leaf Bladementioning
confidence: 99%
“…Sodium and potassium interact at two main levels: the interference of Na + with K + nutrition, and the substitution of Na + for K + as highly dynamic and mobile cellular osmolyte in conditions of K + shortage (Haro et al, 2010;Kronzucker and Britto, 2011;Kronzucker et al, 2013;Alvarez-Aragon et al, 2016). Soil salinity is often associated with elevated levels of Na + (Munns and Tester, 2008).…”
Section: Sodium-potassium Interactionsmentioning
confidence: 99%
“…Soil salinity is often associated with elevated levels of Na + (Munns and Tester, 2008). Although it is not clear what cytosolic levels of Na + are harmful to the plant cell (Kronzucker and Britto, 2011;Alvarez-Aragon et al, 2016), this cation is usually excluded from the cytosol. Due to their physicochemical similarity, Na + and K + can compete for binding to amino acids of protein surfaces, pockets of allosteric regulation or selectivity filters of ion channels (Benito et al, 2014).…”
Section: Sodium-potassium Interactionsmentioning
confidence: 99%
“…A study on barley showed that cytosolic K + /Na + ratios did not explain growth inhibition because of salt stress (Kronzucker et al ). Another study on Arabidopsis showed that growth inhibition because of NaCl treatments was caused by the osmotic component of the treatment rather than the toxic component (Alvarez‐Aragon et al ). In that sense, isotonic combinations of KCl/NaCl were able to inhibit plant growth without giving rise to low K + /Na + ratios.…”
Section: Potassium Deficiency and Salinity Drought And Biotic Stressmentioning
confidence: 99%